Influência do uso da casca do ovo beneficiada como aditivo em varistores à base de ZnO - Silva, Jussiê Ubaldo da (2023)
Varistors are semiconductor devices that have non-linear characteristics, acting as protection devices against voltage transients. There are several types of varistors, but ZnO ones stand out due to their better energy absorption capacity, better nonlinearity coefficients and low residual voltage. Several researches in the area of materials development have been carried out based on the use of waste and this has positive impacts from an economic and environmental point of view. However, the use of waste in the manufacture of varistors has not been reported, hence the importance of exploring the study of waste as an additive in the composition of ZnO varistors. Therefore, the objective of this work is to reduce the amount of additives in the composition of the samples, to study the use of eggshells processed from free-range chickens (COGB), the effects of different sintering conditions, as well as the effect of concentration variation of COGB on the electrical properties and microstructure of the ZnO varistor. The combustion reaction synthesis method was used, a method that stands out for being simple and resulting in fine and homogeneous powders. Samples were developed to study the sintering conditions, their compositions and also the COGB concentration variation. The oxides used to compose the studied samples were ZnO, Bi2O3, CoO, commercial CaO and CaO from farm chicken eggshells. The sintering method used was in two stages, with plateau temperatures T2 = 825 °C and T1 = 900 °C, 950 °C, 1000 °C, 1050 °C and 1100 °C. The concentrations studied were 0.00, 0.50, 1.00, 1.50, 2.00, 2.50 in mol% of COGB. The sintered samples were subjected to electrical tests to survey the curve of current density x electric field in which the non-linear coefficient, leakage current and rupture field of the samples, variation of the dielectric constant, dielectric loss tangent were determined. and impedance values. Microstructure studies were also carried out through X-ray Diffraction - XRD, Scanning Electron Microscopy - SEM, Dispersive Energy Spectroscopy - EDS, Thermogravimetric Analysis - TGA, Differential Exploratory Calorimetry - DSC and granulometric analysis results show that with the using 1.0 mol% of COGB, the samples sintered with T1 = 1000 °C, there was an increase in the nonlinear coefficient from 6.8 to 15 and a reduction in the leakage current from 0.24 mA to 0.054 mA. An increase in the average grain size from 8.28 μm to 9.6 μm was also observed, resulting in a decrease in the rupture field from 3600 V/cm to 2900 V/cm. Regarding the study of sintering conditions, temperatures T1 = 950 °C and T1 = 1100 °C obtained better electrical and morphological results, reaching a nonlinear coefficient equivalent to 60 and 68 respectively. Therefore, it can be seen that the processed eggshell has a positive effect on improving electrical properties and the sintering conditions also contribute to improving these parameters.